A Rare Case of Large Schwannoma of the Parapharyngeal Space - Nora Siupsinskiene; Irina Arechvo; Rimante Lapinskaite; Evaldas Padervinskis; Silvija Ryskiene; Saulius Vaitkus (Case Reports in Otolaryngology)
Schwannoma originating from the peripheral nerves is a rare lesion of the parapharyngeal space. The special traits of the presented case included the following: the patient presented with slowly progressing dysphagia, speech difficulties, jaw numbness, and taste dysfunction. A dislocated lateral pharyngeal wall with mild inflammatory changes of the oropharyngeal mucosa was observed during pharyngoscopy. The radiological and histological characteristics of the neoplasm are consequently presented. Special emphasis is placed on the surgical treatment of the tumor.